ANALISIS PRODUK CACAT MENGGUNAKAN METODE SEVEN TOOLS DALAM MEMBERIKAN LAYANAN BERKUALITAS BERBASIS JAMINAN HALAL PADA PERUSAHAAN BETON TIANG PANCANG - Muhammad Nur Akbar; Anis Saleh; Anshar Daud; Muhammad Basri; Muhammad Nusran (Universitas Mathla’ul Anwar Banten, 2022)
Excellent product and service quality is important in the era of industrial competition to win the competition. Companies must play an important role and WIKA Beton as a leading Pile Construction company in Indonesia and even in Asia has taken part in having 14 factories with 1 mibile Plant. The problem that occurs is that some products are damaged or defective. Due to the low quality of the pile product and defects it will reduce the value of the product. Objective: To find out the cause of the recorded product using the seven tools method. Methods: identification and environmental mapping of the problems causing the occurrence of recorded products. Results and Discussion: Damage and defects in the concrete pile products must be repaired using the 7-Tools method (seven tools. Defective products after using the seven tools can be seen the types of defects that exist such as peeling, corrosion of steel bones, deflection, hollow and porous The secondary causes are due to environmental factors, humans, methods, materials, machines. The secondary causes are significant, namely, the environment is dusty and dirty, dirty air, noisy, and high temperature. Human factors are lack of discipline, tired eyes, lack of thorough, fatigue of workers. On the material, corrosion (rusting) occurs on the reinforcement, the mixture of materials changes in volume, evaporation of water in the concrete mixture, the thickness of the concrete blanket is too large. Applying 5S, improving work position, monitoring temperature during production, checking and cleaning tools after use, checking the machine every week by the maintenance division Conclusion: the cause of the occurrence note products are due to primary and secondary factors as well as halal awareness factors in the scope of work and work processes, it is very possible to create superior performance based on halal knowledge (halal knowledge), so that the seven tools can be equipped with Halal awareness factors as factors that affect performance towards zero product notes on the concrete product